2021
DOI: 10.1016/j.ctro.2021.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Value of 18F-fluorocholine PET/CT in predicting response to radical radiotherapy in patients with localized prostate cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…We found that TLCKA of the primary lesion was the only VP able to predict biochemical recurrence. This is consistent with the results published by Sepulcri et al [ 38 ] who reported that TLCKA of primary tumors in [ 18 F]F-choline PET/CT staging was a predictor of BCR after radiation therapy. TLCKA of the primary tumor reflects both the local extension of PCa as well as its choline metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…We found that TLCKA of the primary lesion was the only VP able to predict biochemical recurrence. This is consistent with the results published by Sepulcri et al [ 38 ] who reported that TLCKA of primary tumors in [ 18 F]F-choline PET/CT staging was a predictor of BCR after radiation therapy. TLCKA of the primary tumor reflects both the local extension of PCa as well as its choline metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…However, growing evidence supports the use of risk stratification tools that combine clinical parameters, genomic biomarkers, and morphological and functional features able to either optimize health care or predict BCR in PCa patients [31][32][33][34]. Nevertheless, the lack of validation of these predictive tools in prospective randomized clinical trials represents the main limitation of their introduction in clinical practice.…”
Section: Discussionmentioning
confidence: 99%